Empowering Communities through Ecotourism: A Holistic Model for Sustainable Development - Erdawati, Mega; Ayub, Zulkifli (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study explores a holistic model of community empowerment through ecotourism as a sustainable development strategy in Bulu Tanah Pine Forest, Bone Regency, Indonesia. Using a qualitative approach with a case study method, this research involved 15 informants selected by purposive sampling, consisting of 5 tourists, 5 stakeholders, and 5 members of the environmental community. Data were collected through in-depth interviews and direct observation in the field. The results showed that community-based ecotourism not only contributes to environmental conservation, but also improves the economic and social welfare of local communities. Tourists and local communities play an active role in conservation activities and sustainability promotion, while stakeholders play a role in providing support, both in the form of facilities and technical training. Community empowerment through ecotourism has proven to be an effective approach in maintaining a balance between economic, social and environmental interests. This research offers guidance for the development of sustainable ecotourism by integrating various stakeholders to create wider benefits for local communities and the environment.